2021
DOI: 10.1111/ijcp.14861
|View full text |Cite
|
Sign up to set email alerts
|

A study on stress and resilience among hearing‐impaired people during the COVID‐19 pandemic

Abstract: Stress is defined as the natural reaction of the body in the presence of any danger that requires adaptation. 1 It has been proven to have adverse effects on health and mental well-being. 2 Psychological resilience is defined as the adaptation and coping skills of the individual when faced with stressful situations. 3 The functioning of stress and psychological resilience has been studied in some population groups at risk, such as people affected by traumatic events (eg violence) 4 and those with chronic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 40 publications
(53 reference statements)
1
12
0
2
Order By: Relevance
“…30 COVID-19 döneminde yapılan başka bir çalışmada, işitme cihazı kullanan bireylerin mental olarak stres ve dayanıklılıkta sağlıklı bireylere göre daha fazla etkilendiği bulunmuştur. 31 Ek olarak, Wilson ve ark.nın yaptığı çalışmada da Kİ kullanıcılarının büyük çoğunluğunun COVID-19 pandemi dönemi boyunca mental durumlarını olumsuz etkilediği bildirilmiştir. 32 Bu kapsamda uygun sağlık kuruluşlarına ulaşımındaki engeller, randevu süreçlerinde gecikmeler ve buna bağlı olarak "fitting" seanslarının aksaması gibi süreçlerin Kİ kullanıcılarında mental sağlığın daha fazla etkilenmesi beklentisini doğurmuştur.…”
Section: çAlişma Di̇zayniunclassified
See 1 more Smart Citation
“…30 COVID-19 döneminde yapılan başka bir çalışmada, işitme cihazı kullanan bireylerin mental olarak stres ve dayanıklılıkta sağlıklı bireylere göre daha fazla etkilendiği bulunmuştur. 31 Ek olarak, Wilson ve ark.nın yaptığı çalışmada da Kİ kullanıcılarının büyük çoğunluğunun COVID-19 pandemi dönemi boyunca mental durumlarını olumsuz etkilediği bildirilmiştir. 32 Bu kapsamda uygun sağlık kuruluşlarına ulaşımındaki engeller, randevu süreçlerinde gecikmeler ve buna bağlı olarak "fitting" seanslarının aksaması gibi süreçlerin Kİ kullanıcılarında mental sağlığın daha fazla etkilenmesi beklentisini doğurmuştur.…”
Section: çAlişma Di̇zayniunclassified
“…Bu bulgular, Kaya ve ark.nın yapmış olduğu çalışma ile uyumlu elde edilmemiştir. 31 Çalışmada, gelir seviyesinde değişiklik, yaş ve cinsiyet faktörlerinin stres faktörünü ortaya çıkarmada işitme cihazı kullanıcılarının sağlıklı bireylere kıyasla daha fazla etkilendiğini bulmuşlardır. 31 Bu durumun nedeni, çalışmalarda farklı ölçeklerin kullanılmasından ve bu ölçeklerin yaşam kalitesinin farklı yönlerini değerlendirmiş olmasından kaynaklandığı düşünülmektedir.…”
Section: çAlişma Di̇zayniunclassified
“…This has had significant implications for healthcare systems largely due to its very high transmission rate. 1,2 This has resulted in changes in daily practice within healthcare institutions and services. 2 Nations have focused on reducing viral transmission and avoiding hospitalizations and SARS-CoV-2-related deaths.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 This has resulted in changes in daily practice within healthcare institutions and services. 2 Nations have focused on reducing viral transmission and avoiding hospitalizations and SARS-CoV-2-related deaths. 1 This has led to several societal restrictions and protective measures to limit transmission amongst the public.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, mask use, language, technology inaccessibility, and social connection, each contribute to the increased need for psychosocial adjustment for DHH people during the pandemic. This adjustment has caused introduced other intersecting negative impacts on their mental health including loneliness, anxiety disorders, stress, aggression, and depressive symptoms (Al Majali & Alghazo, 2021;Anderson et al, 2021;Ariapooran & Khezeli, 2021;Kaya et al, 2021;Littlejohn et al, 2021;Yang et al, 2021). Naylor et al (2020), concluded that, "we find that there are many negative, and a few positive effects of COVID-19 restrictions and safety measures on people with hearing loss.…”
Section: Discussionmentioning
confidence: 99%